2009
DOI: 10.1038/hdy.2009.174
|View full text |Cite
|
Sign up to set email alerts
|

Heritable artificial sex chromosomes in the medaka, Oryzias latipes

Abstract: Chromosomal sex determination is widely used by vertebrates, however, only two genes have been identified as master sex-determining genes: SRY/Sry in mammals and DMY in the teleost medaka. Transfer of both genes into genetically female (XX) individuals can induce male development. However, transgenic strains have not been established in both cases because of infertility of the transgenic founders in mammals and low germline transmission rates in medaka. In this study, we used a BAC clone containing DMY in a 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Green fluorescent protein (GFP) was used as a fluorescent reporter under the control of the medaka olvas promoter (Tanaka et al 2001). We constructed a recombinant plasmid where vasa-GFP was inserted into the pCC1 vector in an earlier study (Otake et al 2010). In the present study, we amplified this region using PCR and the following primer sets: 5′-TAG CGA TGA GCT CGG ACT TCC ATT GTT CA-3′ and 5′-CGT AAT CAT GGT CAT AGC TGT TTC CTG TGT-3′.…”
Section: Transgenesismentioning
confidence: 99%
“…Green fluorescent protein (GFP) was used as a fluorescent reporter under the control of the medaka olvas promoter (Tanaka et al 2001). We constructed a recombinant plasmid where vasa-GFP was inserted into the pCC1 vector in an earlier study (Otake et al 2010). In the present study, we amplified this region using PCR and the following primer sets: 5′-TAG CGA TGA GCT CGG ACT TCC ATT GTT CA-3′ and 5′-CGT AAT CAT GGT CAT AGC TGT TTC CTG TGT-3′.…”
Section: Transgenesismentioning
confidence: 99%
“…Sex-linkage analysis of the transgenic strains of Otake et al indicated that exogenous DMY was located on LG5 in one strain, and LG23 in another (Otake et al, 2010). Real-time PCR experiments confirmed that DMY is only expressed in the testes of transgenic strains, and that they have multiple copies of DMY and higher DMY expression levels than wild-type medaka.…”
mentioning
confidence: 60%
“…Even the neo-Y chromosome of Drosophila miranda is 41 million years old (Bachtrog and Charlesworth, 2002), whereas 'young' sex chromosomes of fish are in excess of 10 million years old (for example, Tanaka et al, 2007), so we can only bear indirect witness to their evolution. As reported in this issue, researchers in Japan have developed a more practicable alternative to time travel by creating the first vertebrate heritable artificial sex chromosomes in the medaka, Oryzias latipes (Otake et al, 2010). In doing so, they open a new and exciting chapter in sex chromosome research.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dmy is the Y-specific paralog of the autosomal Dmrt1 gene which appears to be involved in male sexual development in vertebrates (Nanda et al, 2002). Mutations with impaired Dmy function cause XY sex reversal (Shinomiya et al, 2004;Otake et al, 2006Otake et al, , 2008 and the presence of an exogenous Dmy gene induces XX sex reversal (Matsuda et al, 2007;Otake et al, 2009), suggesting that this gene is necessary and sufficient to induce testicular development. Dmy contains a DNA-binding motif (the DM domain), and is thus thought to encode a putative transcription factor that activates or represses downstream target genes to regulate sexual differentiation of the bipotential gonad.…”
Section: Introductionmentioning
confidence: 99%